Remittances and Economic Growth: Exploring the Role of Financial Development - Zakia Batool; Muhammad Haroon; Sajjad Ali; Rashid Ahmad (iRASD Journal of Management, 2022)
Over the last several decades, the amount of international migration has increased dramatically, resulting in enormous cash flows to labour-exporting nations. The importance of remittances in sustaining families in poor nations has been well acknowledged by many researchers but at the same time a well-functioning banking system has been deemed important to increase migrant transfers by lowering prices and improving service availability. Therefore, this study attempts to analyse the role of financial sector development in enhancing the effect of remittances in spurring economic growth. This study uses time series data for the period of 198-2020 to delve into the nexus. Using ARDL approach, this study finds the complementary role of remittances and financial sector in both long run and short run.